2021
DOI: 10.1088/1361-6528/ac07cf
|View full text |Cite
|
Sign up to set email alerts
|

MnSn2 and MnSn2–TiO2 nanostructured anode materials for lithium-ion batteries

Abstract: The high theoretical lithium storage capacity of Sn makes it an enticing anode material for Li-ion batteries (LIBs); however, its large volumetric expansion during Li–Sn alloying must be addressed. Combining Sn with metals that are electrochemically inactive to lithium leads to intermetallics that can alleviate volumetric expansion issues and still enable high capacity. Here, we present the cycling behavior of a nanostructured MnSn2 intermetallic used in LIBs. Nanostructured MnSn2 is synthesized by reducing Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…XRD patterns corresponding to these samples showing MnSn 2 phase purity are shown in Figure S8. We have previously demonstrated that for MnSn 2 nanoparticles, brief air exposure (5 min) results in oxidation and segregation of Mn to the surface, forming a β–Sn core and mixed Mn–Sn oxide shell . Such behavior suggests an instability of MnSn 2 toward phase separation under ambient conditionsthis is unusual among intermetallic materials, which typically have enhanced compositional stability due to the relaxed free energy arising from atomic ordering.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…XRD patterns corresponding to these samples showing MnSn 2 phase purity are shown in Figure S8. We have previously demonstrated that for MnSn 2 nanoparticles, brief air exposure (5 min) results in oxidation and segregation of Mn to the surface, forming a β–Sn core and mixed Mn–Sn oxide shell . Such behavior suggests an instability of MnSn 2 toward phase separation under ambient conditionsthis is unusual among intermetallic materials, which typically have enhanced compositional stability due to the relaxed free energy arising from atomic ordering.…”
Section: Resultsmentioning
confidence: 99%
“…For MnSn 2 nanoparticles, adding W­(CO) 6 to the reaction solution and increasing Sn­[N­(SiMe 3 ) 2 ] 2 concentration resulting in a decrease of mean nanoparticle size to 22 ± 3 nm (Figure D). In our initial report describing MnSn 2 nanoparticle synthesis, the same reaction without W­(CO) 6 resulted in much larger nanoparticles, with a mean size of 76 ± 16 nmthis further supports the role of W­(CO) 6 as a nucleating agent . Otherwise, reducing the amount of OLA used from 0.3 to 0.2 mmol, lowering the OLA/Sn 2+ ratio, resulting in mean nanoparticle size increasing to 48 ± 4 nm (Figure E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations